2018
DOI: 10.1186/s12864-018-4834-3
|View full text |Cite
|
Sign up to set email alerts
|

The whole transcriptome effects of the PPARα agonist fenofibrate on livers of hepatocyte humanized mice

Abstract: BackgroundThe role of PPARα in gene regulation in mouse liver is well characterized. However, less is known about the role of PPARα in human liver. The aim of the present study was to better characterize the impact of PPARα activation on gene regulation in human liver. To that end, chimeric mice containing hepatocyte humanized livers were given an oral dose of 300 mg/kg fenofibrate daily for 4 days. Livers were collected and analyzed by hematoxilin and eosin staining, qPCR, and transcriptomics. Transcriptomics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 57 publications
2
20
1
Order By: Relevance
“…It was assumed that human coactivators/repressors regulate the action of PPAR-α in a humanized way [80,81]. Later, it was shown that PPAR-α activation in human hepatocytes occurred in a more moderate way than in the residual mouse hepatocytes, confirming the abovementioned hypotheses [82].…”
Section: Ppar-targeted Preclinical Drug Testingmentioning
confidence: 68%
“…It was assumed that human coactivators/repressors regulate the action of PPAR-α in a humanized way [80,81]. Later, it was shown that PPAR-α activation in human hepatocytes occurred in a more moderate way than in the residual mouse hepatocytes, confirming the abovementioned hypotheses [82].…”
Section: Ppar-targeted Preclinical Drug Testingmentioning
confidence: 68%
“…Analysis of mRNA levels of PPARα target genes in the livers of naïve and fenofibrate treated sgp130Fc and WT mice confirmed the fenofibrate stimulated increase in PPARα activity. Most of the evaluated PPARα target genes in the liver, including Cyp4a10, Cyp4a14, Fabp3, Fatp, L-Fabp and Vnn1 (de la Rosa Rodriguez et al, 2018; Martin et al, 1997; Montagner et al, 2016; van Diepen et al, 2014; Vida et al, 2013), were strongly elevated by fenofibrate (Figure S7); but interestingly, did not have the same effect on Cpt-1 and Apoe (Figure S7). Importantly, fenofibrate treatment reduced the excess body weight (Figure 7B) and gonadal fat pad weight (Figure 7B,C) of sgp130Fc mice, bringing them to levels identical to those of fenofibrate treated WT mice, whose weight was also reduced by about 14 percent in comparison to untreated WT littermate controls.…”
Section: Resultsmentioning
confidence: 97%
“…HADHA, an enzyme that has the enoyl-CoA hydratase and hydroxyacyl-CoA dehydrogenase activities as ECH-1.1 in C. elegans , is responsible for the last three steps of mitochondrial β-oxidation of long chain fatty acids ( Fould et al., 2010 , de la Rosa Rodriguez et al., 2018 ). Consistently, it was reported that daily intake of a PPARα agonist (fenofibrate) upregulated the gene expression of HADHA in humanized liver of chimeric mice after 4 days ( de la Rosa Rodriguez et al., 2018 ). Thus, the upregulation of ech-1.…”
Section: Discussionmentioning
confidence: 99%